Cube-Type Algebraic Attacks on Wireless Encryption Protocols. - Petrakos, Nikolaos; Dinolt, George W.; Michael, James Bret; Stanica, Pantelimon (Computer (00189162), 2009)
The article explains how to formally evaluate the strengths of a given cryptosystem to ensure that no flaws have entered into the application. It describes the several attacks that have been implemented on the Bluetooth system and the successes of such attacks in defeating the cryptosystems used by the Institute of Electrical and Electronics Engineers (IEEE) 802.11 and 802.16 technologies. The phases of completing cube-type algebraic attacks on wireless encryption protocols are also discussed.